(untitled) (Música Hodie, 2018)
This paper addresses a high-level discussion about the links between Science and Music, focusing on my own sonification and auditory display practices around air quality. Grounded on recent insights on interdisciplina- rity and sonification practices, the first sections will point out some potential contributions from scientific research to music studies and vice versa. I will propose the concept of mutualism to depict the interdependent status of Mu- sic and Science. The final sections will discuss air contamination as a complex contemporary problem, and will re- port three practice-based-design projects, AirQ jacket, Esmog Data and Breathe!, which outline different directions in facing local environmental awareness.